The Implications Of The Change In The Age Limit Regulation On Child Marriage Practices In Sungai Rengit Village, Banyuasin Regency - Ulya, Fadhilatul; Huzaimah, Arne; Ramelan, Rafida (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2026)
Child marriage continues to occur in rural communities, including in Sungai Rengit Village, Talang Kelapa Subdistrict, Banyuasin Regency, despite the government’s enactment of the amendment to Law Number 16 of 2019, which raises the minimum legal age of marriage to 19 years for both men and women. While many studies discuss the normative aspects of child marriage, empirical research on the policy's effectiveness at the local rural level (law in action) remains limited. This study aims to analyze the implications of the change in the legal age of marriage and the factors contributing to the persistence of child marriage in the village. The research employs a juridical-empirical method with a qualitative approach through the collection of primary data in the form of interviews and documentation involving community members who engaged in early marriage, as well as secondary data derived from literature and statutory regulations. The findings indicate that the change in the age requirement has had positive impacts, including increased legal awareness among the community and a decline in the incidence of child marriage. However, early marriage continues to occur due to social and economic pressures, low levels of education, premarital pregnancy, unregistered marriages, limited legal literacy, insufficient knowledge of reproductive health, and the absence of institutions dedicated to the protection of women and children. These findings highlight the emergence of unintended policy consequences, namely an increase in unregistered marriages, and provide a theoretical contribution to the socio-legal literature regarding structural vulnerabilities in policy implementation in developing countries.